2001
DOI: 10.1021/bi0103922
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metal Ions in Catalysis by Enolase:  An Ordered Kinetic Mechanism for a Single Substrate Enzyme

Abstract: Spectroscopic and kinetic methods have been used to explore the roles of divalent metal ions in the enolase-catalyzed dehydration of 2-phosphoglycerate (2-PGA). Enolase requires 2 equiv of metal ion per active site for maximal activity. Previous crystallographic studies [Larsen, T. M., Wedekind, J. E., Rayment, I., and Reed, G. H. (1996) Biochemistry 35, 4349-4358] showed that both magnesium ions coordinated to the carboxylate group of the substrate/product-a scheme consistent with metal ion assistance in form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 45 publications
5
49
0
Order By: Relevance
“…This time would be within the dead time of the stopped-flow, as no lag phase has been observed by them or by us. Our data show no inhibition of the TSP reaction at Mg 2+ concentrations (30 mM) that are inhibitory to the steady-state physiological reaction, that is, there is no evidence for binding of inhibitory Mg 2+ , consistent with the interpretation of Poyner et al [18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This time would be within the dead time of the stopped-flow, as no lag phase has been observed by them or by us. Our data show no inhibition of the TSP reaction at Mg 2+ concentrations (30 mM) that are inhibitory to the steady-state physiological reaction, that is, there is no evidence for binding of inhibitory Mg 2+ , consistent with the interpretation of Poyner et al [18].…”
Section: Discussionsupporting
confidence: 91%
“…Originally, we wished to see if Mg 2+ concentrations above 1 mM inhibited the TSP reaction; in other words, is the inhibition of the physiological reaction due to slowing product (PEP) release [5,18], or, a possibility suggested by Faller et al [2], due to binding of a third, inhibitory Mg 2+ at the active site?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were later proved in Lebioda and Reed laboratories when the crystalline structures of yeast enolase and neuron-specific human enolase were established [2,45,46]. Selective mutagenesis of yeast enolase and its recent crystallographic studies revealed that the basic amino-acids Lys345, Lys396, His159, His373, and Arg374 in the catalytic center are important in the mechanism of the reversible transition of 2-PGA to PEP.…”
Section: Discussionmentioning
confidence: 88%
“…Magnesium ions play a double role in enolases. The so-called conformational ions ensure the proper spatial structure of the active center, whereas the catalytic ions are necessary for the reaction mechanism [45,46]. They ensure the insertion of the substrate into catalytic pocket and its transformation to the reaction product [50].…”
Section: Discussionmentioning
confidence: 99%